2014
DOI: 10.14260/jemds/2014/4048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Ferritin in Patients of Coronary Artery Disease

Abstract: BACKGROUND: Serum ferritin, which measures stored iron, is an inflammatory marker and a potential novel risk factor for CAD. Its role in coronary artery disease like acute myocardial infarction has generated considerable interest in recent times. There is a plethora of articles reporting the relationship between serum ferritin and acute myocardial infarction but with conflicting and contradictory results. AIMS AND OBJECTIVES: 1) To compare serum ferritin levels in cases of coronary artery disease with those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…There are, however, conflicting data with regard to the various roles of ferritin as a biomarker in a number of diseases. Thus, while previous studies presented data that supported a positive association between high serum ferritin levels and the development and progression of chronic diseases, like cardiovascular disease (CAD) and diabetes [23,24], results from other studies either failed to show such a relationship or found an inverse association whereby low ferritin levels correlated with the development of CAD and other chronic diseases [25,26]. It remains to be seen whether ferritin acts as a bystander or a causative factor in the development of heart failure.…”
Section: Introductionmentioning
confidence: 98%
“…There are, however, conflicting data with regard to the various roles of ferritin as a biomarker in a number of diseases. Thus, while previous studies presented data that supported a positive association between high serum ferritin levels and the development and progression of chronic diseases, like cardiovascular disease (CAD) and diabetes [23,24], results from other studies either failed to show such a relationship or found an inverse association whereby low ferritin levels correlated with the development of CAD and other chronic diseases [25,26]. It remains to be seen whether ferritin acts as a bystander or a causative factor in the development of heart failure.…”
Section: Introductionmentioning
confidence: 98%